TRATAMENTO AGUDO COM CAFEÍNA E L-ARGININA REDUZ OS NÍVEIS GLICEMICOS EM RATOS OBESOS SUBMETIDOS AO EXERCÍCIO AERÓBICO - Luiz Augusto da Silva; José Augusto Pochapski; Allan Raczenski; Leandro Coelho Lemos; Leandro de Freitas; Camila Eltchechem; Carlos Ricardo Maneck Malfatti (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction: Obesity is a major risk factor for metabolic syndrome. This syndrome comprises a group of conditions including insulin resistance, diabetes type two and hypertension. Obese individuals may develop in parallel insulin resistance with obesity, while it remains normal glucose tolerance, the pancreatic beta cells to increase production and secretion of insulin as a compensatory mechanism. Studies have shown positive effects of caffeine and L-arginine on the reduction in glucose tolerance and increased insulin sensitivity. Methods: We used 10 adult male Wistar rats, 4-month-old boy with obesity induced by monosodium glutamate (MSG). We conducted a swim test lasting 30 minutes and measured blood glucose levels before and after exercise and supplementation. Results: The animals that received caffeine reduced (14%), for L-Arg was reduced to L-Arg was reduced (10%) or placebo (65%). Conclusion: The results showed that acute caffeine intake could be modifying the availability or glucose metabolism in obese mice along with exercise, however these data should be supplemented in the new study however try to follow the results of studies in the literature.